Congenital Perineal Groove Defect in Monozygotic Twin Infants: A Literature Review - Mimily Harsono; David Yanishevski; Massroor Pourcyrous (Thieme Medical Publishers, Inc., 2021)
Perineal groove is a rare benign congenital anomaly with lesion that resembles perforation of mid-perineum or perineal raphe area. Most reported cases of congenital perineal groove presented as an isolated defect in term or early-term singleton female infants. Thus far, there is no reported case of this anomaly in monozygotic twins. Embryo pathogenesis of this female predominance congenital defect remains controversial. Many clinicians are unfamiliar with this congenital anomaly. This congenital defect tends to get self-resolved at around 2 year of age. Nevertheless, the exposed nonepithelized mucous membrane can carry risk of local infection or irritation with the possibility of requiring early surgical correction. The defect can be infrequently associated with other ano-urogenital malformations that required immediate surgical intervention. Most isolated cases tend to be asymptomatic and self-healed with expectant management. Surgical correction may be considered if not healed after 2 years of age. Early diagnosis at birth is important to avoid misdiagnoses at later age for trauma, dermatitis, sexual abuse, and risk of unnecessary aggressive intervention. Early parental counseling for providing good hygiene and close follow-up is important to prevent infection or inflammation. Presentation of this anomaly in both monozygotic twins may support the hypothesis of potential disruption during embryo morphogenesis stages.